Evaluation of the Partial Replacement of Dietary Fish Meal With Fermented or Untreated Soybean Meal in Juvenile Silver Barb, Barbonymus gonionotus - Jahan, Halima; Tumpa, Israt Jahan; Qasem, Wafaa A.; Moniruzzaman, Mohammad; Pervin, Mst. Arzu; Akter, Rabeya; Omri, Abdelwahab; Min, Taesun; Hossain, Zakir (Frontiers in Nutrition, 2021)
Fish meal (FM) has excellent protein and lipid profile. However, FM is losing its acceptability and substituted with plant protein due to FM has high price, high demand and sustainability issues in global aquaculture production. In this study, experimental diets were prepared by substituting FM with fermented soybean meal (FSM) or normal and un-treated soybean meal (SM) to assess the effects on growth, hematology, innate immunity, gut physiology and digestive enzyme activities in juvenile silver barb, Barbonymus gonionotus. Five diets i.e. 40% FM (FM 40), 20% FM+20% FSM, (FM 20+FSM 20), 20% FM+20% SM (FM 20+SM 20), 40% FSM (FSM 40) and 40% SM (SM 40) were fed the fish twice daily for 90 days. After 90-days of feeding trial, FM 40, FM 20+FSM 20 and FM 20+SM 20 diet groups showed significantly higher weight gain and specific growth rate compared to the FSM 40 and SM 40 diets. Hepatosomatic index and viscerosomatic index were significantly higher in fish fed with the FSM 40 and SM 40 diets than those of fish fed with the FM 40 diet. Hematocrit, hemoglobin and erythrocyte count were significantly lower in fish fed with the SM 40 diet compared to fish fed with the FM 40 and FM 20+FSM 20 diets. Superoxide dismutase and catalase activities in the liver were significantly higher in fish fed with the SM 40 diet compared to fish fed with the FM 40 diet. However, serum thiobarbituric acid reactive substances in fish fed with the experimental diets were unaltered. Fish showed significant reduction of villus height in the anterior and posterior intestine of fish fed with the FSM 40 and SM 40 diets, whereas muscular thickness was opposite to the findings of villus height. Digestive enzyme activities in intestine were significantly higher in fish fed with the FM 40 diet compared to those in the SM 40 diet. The results of the present study revealed that the 50% of FM can be replaced by FSM or SM as a source of protein without affecting the growth of juvenile silver barb.